Comparative analysis of different methods for evaluating quality of Quercus ilex seedlings inoculated with Tuber melanosporum - Andres-Alpuente, Antonio; Sanchez, Sergio; Martin, Maria; Javier Aguirre, Angel; Barriuso, Juan J. (MYCORRHIZA, 2014)
The quality of seedlings colonized by Tuber melanosporum is one of the main factors that contributes to the success or failure of a truffle crop. Truffle cultivation has quickly grown in European countries and elsewhere, so a commonly shared seedling evaluation method is needed. Five evaluation methods are currently published in the literature: three are used in Spain and two in France and Italy. Although all estimate the percentage colonization by T. melanosporum mycorrhizae, they do it in different ways. Two methods also estimate total number of mycorrhizae per seedling. Most are destructive. In this work, ten batches of holm oak seedlings inoculated with T. melanosporum from two different nurseries were evaluated by means of the five methods noted above. Some similarity was detected between the percentages of T. melanosporum mycorrhizae estimated by each method but not in their ability to assess the suitability of each batch. We discuss the advantages and disadvantages for each method and suggest approaches to reach consensus within the truffle culture industry for certifying mycorrhizal colonization by T. melanosporum and seedling quality.
The following values have no corresponding Zotero field: pub-location: 233 SPRING ST, NEW YORK, NY 10013 USA publisher: SPRINGER
Keywords: Black truffle; Certification; Holm oak; Mycorrhization; Nurseries; Truffle culture